Comparative genomics defines the core genome of the growing N4-like phage genus and identifies N4-like Roseophage specific genes - Chan, Jacqueline Z.-M.; Millard, Andrew D.; Mann, Nicholas H.; Schäfer, Hendrik (Frontiers in Microbiology, 2014)
Two bacteriophages, RPP1 and RLP1, infecting members of the marine Roseobacter clade were isolated from seawater. Their linear genomes are 74.7 and 74.6 kb and encode 91 and 92 coding DNA sequences, respectively. Around 30% of these are homologous to genes found in Enterobacter phage N4. Comparative genomics of these two new Roseobacter phages and 23 other sequenced N4-like phages (three infecting members of the Roseobacter lineage and 20 infecting other Gammaproteobacteria) revealed that N4-like phages share a core genome of 14 genes responsible for control of gene expression, replication and virion proteins. Phylogenetic analysis of these genes placed the five N4-like roseophages (RN4) into a distinct subclade. Analysis of the RN4 phage genomes revealed they share a further 19 genes of which nine are found exclusively in RN4 phages and four appear to have been acquired from their bacterial hosts. Proteomic analysis of the RPP1 and RLP1 virions identified a second structural module present in the RN4 phages similar to that found in the Pseudomonas N4-like phage LIT1. Searches of various metagenomic databases, including the GOS database, using CDS sequences from RPP1 suggests these phages are widely distributed in marine environments in particular in the open ocean environment.